PELAKSANAAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA BALAI HARAPAN KECAMATAN TEMPUNAK KABUPATEN SINTANG: PELAKSANAAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA BALAI HARAPAN KECAMATAN TEMPUNAK KABUPATEN SINTANG - S.S, Antonius (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
The objective of this study is to determine and describe the implementation of community participation in development in Balai Harapan Village, Tempunak District, Sintang Regency, including: participation in development planning, participation in development implementation, participation in development supervision, and participation in the utilization and maintenance of village development. The method used is descriptive research with a qualitative approach. The subjects of this study consisted of the Balai Harapan Village Head, the Village Secretary, the Head of Development, and members of the Balai Harapan Village community. Data collection techniques included observation, interviews, and documentation studies. Data analysis used qualitative descriptive analysis methods. The results of this study indicate that participation in development planning is implemented through a village development planning deliberation mechanism involving all elements in Balai Harapan Village. Participation is implemented only through contributions of labor and attendance at village meetings. Development supervision has not been implemented according to existing standards and procedures, limited to input and suggestions. Community awareness of maintaining village development assets is still low, as many development projects are often undertaken without community involvement in their preparation.